The Influence of Product Innovation and Marketing Strategy on the Competitiveness of MSMEs - Wartini, Sri; Suseno, Dewi Alima Nostalia (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the effect of product innovation and marketing strategy on the competitiveness of MSMEs in Indonesia, both partially and simultaneously. A causal quantitative approach was employed, with data collected through an online questionnaire distributed via Google Form to 100 MSME owners selected using purposive sampling. The research instruments were developed using a five-point Likert scale based on Gunday et al. (2011) for product innovation (10 items), Kotler & Keller (2016) for marketing strategy (12 items), and Porter (1990) for MSME competitiveness (10 items). Following validity and reliability testing, data were analyzed using multiple linear regression with R statistical software. The results indicate that: (1) product innovation has a positive and significant effect on MSME competitiveness (β = 0.351; t = 4.807; p < 0.001); (2) marketing strategy has a positive and significant effect on MSME competitiveness (β = 0.538; t = 7.368; p < 0.001); and (3) simultaneously, product innovation and marketing strategy significantly affect MSME competitiveness with F = 58.200 (p < 0.001) and R² = 0.545, indicating that both variables explain 54.5% of the variation in MSME competitiveness. These findings imply that MSMEs in Indonesia need to synergistically integrate product innovation capabilities and digital marketing strategies to achieve sustainable competitiveness.